สภาพการบริหารโรงเรียนอนุบาลนานาชาติมัลเบอรี่เฮ้าส์ ตามเกณฑ์คุณภาพการศึกษาเพื่อการดำเนินการที่เป็นเลิศ - แซ่เตีย, กมลพร; ศรีสุทธิยากร, สิวะโชติ (An Online Journal of Education, 2018)
The purposes of the research were to study current states administration of Mulberry House International Preschool based on the Education Criteria for Performance Excellence. The study populations were in Mulberry House International Preschool. The respondents were 2 School Principals, 8 Teachers and 20 Staffs, total were 30 people. The research instrument is questionnaires for research Approach for Management Development of Mulberry House International Pre-school According to Education Criteria for Performance Excellence. The research instrument were checklist and Rating scale. Data were analyzed by descriptive statistics from frequency, percentage, mean and standard deviation. According to the research results, current states administration of Mulberry House International Preschool base on the Education Criteria for Performance Excellence (EdPex) all in standard. The strength of the school were have high level (over 4.00) 1) Leadership, 3) Costumer focus and 2) Strategic Planning. The weakness were have low level (under 4.00) 7) Results, 5) Workforce Focus, 4) Measurement Analysis and Knowledge Management and 6) Operations Focus